Prediction of race performance of elite cross-country skiers by lean mass - Carlsson, M.; Carlsson, T.; Hammarström, D.; Malm, C.; Tonkonogi, M. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To investigate the relationship between race performance and lean mass (LM) variables, as well as to examine sex differences in body composition in elite-standard cross-country skiers. Methods: Thirty-four elite cross-country skiers (18 men and 16 women) underwent a dual-emission X-ray-absorptiometry body-composition test to determine LM, fat mass, and bone mineral content. For both sexes, performance data were collected from a sprint prologue and a distance race. Results: The absolute expression of LM variables (whole-body [LMWB], upper body [LMUB], and lower body [LMLB]) was significantly correlated with finishing time in the sprint prologue independent of sex. Distance-race performance was significantly related to LMWB, LMUB, and LMLB in women; however, no correlation was found in men. Men had a significantly higher LM and lower fat mass, independent of expression (absolute or relative), for the whole body, arms, trunk, and legs, except for the absolute fat mass in the trunk. Conclusions: The absolute expressions of LMWB, LMUB, and LMLB were significant predictors of sprint-prologue performance in both sexes, as well as of distance-race performance in women only. Compared with women, male skiers have a higher LM in the body segments that are major contributors to propelling forces. These results suggest that muscle mass in the lower and upper body is equally important for race performance; thus, more focus of elite skiers` training should be directed to increasing whole-body muscle mass to improve their competitive performance capability.